MODEL DAN PEMANFAATAN PENELITIAN ETNOGRAFI DALAM DUNIA PENDIDIKAN - Reksiana Reksiana (Almarhalah | Jurnal Pendidikan Islam, 2021)
AbstractThis study discusses about the ethonographic approach in educational research. Ethnographic research, at first, was widely used in anthropological research, and developed in various fields of science such as medicine, health, psychology, and education and other social sciences. then, it can be concluded that there are four types of ethnographic research analysis in Spredley's model, they are: domain analysis, taxonomic analysis, compound analysis, and model analysis (ethnographic results. The qualitative research stages of the Spradley model consisted of 12 stages starting with determining a reliable or accurate key informant. Next, do an interview. Then, the researcher began asking descriptive questions, with an analysis of the interview. The results of the interview analysis, then the researcher conducted a domain analysis. In the next step, the researcher has determined the focus, and conduct a taxonomic analysis, then the researcher asks contrast questions, which are followed by a comparative analysis. The results of the comparative analysis, then the researcher found cultural themes. And the final step, the researcher wrote an ethnographic research report. And of course all of these stages must be adjusted to the field of education if research is in the field of education.Keyword: Ethnography Research, Ethnography Approach, Etnografi in Education.